Hepatocyte Nuclear Factor-1 as Marker of Epithelial Phenotype Reveals Marrow-Derived Hepatocytes, but Not Duct Cells, After Liver Injury in Mice - Swenson, E. Scott (2008)
The potential bone marrow origin of hepatocytes, cholangiocytes, and ductal progenitor cells in the liver was examined in female mice after transplantation of bone marrow cells from male green fluorescent protein (GFP) transgenic donors. Following stable hematopoietic engraftment, the livers of the recipients were injured with carbon tetrachloride (CCl(4), with or without local irradiation of the liver) or 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC, with or without local irradiation of the liver). The presence of numerous marrow-derived, GFP-positive inflammatory cells had the potential to lead to erroneous interpretation of marrow-derived hepatocytes, cholangiocytes, and ductal progenitor cells. Identification of marrow-derived ductal progenitor or cholangiocyte phenotype using colocalization of GFP or Y chromosome with pancytokeratin staining also failed to distinguish epithelial cells from closely apposed inflammatory cells. To address this inadequacy, we developed a rigorous new immunofluorescence protocol to identify marrow-derived epithelial cells in the liver using Y chromosome (donor marker) and hepatocyte nuclear factor-1 (HNF1, a nuclear marker of liver epithelial, nonhematopoietic phenotype). Using the Y/HNF1 method, rare (approximately one in 20,000) hepatocytes in female mice transplanted with male bone marrow contained a donor-derived Y chromosome. On the other hand, no Y chromosomes were found in cholangiocytes or ductal progenitor cells in mice with liver injury due to DDC or CCl(4). The use of a nuclear marker of mature hepatocytes or cholangiocytes, such as HNF1, improves discrimination of marrow-derived epithelial cells in tissue sections.